National Heritage Week thanksgiving church service - Honourable Olivia Grange, CD, MP.
This is an invitation programme that was done by the Minister of Culture,Gender, Entertainment and Sport, Honourable Olivia Grange, that invited persons to the National Heritage Week Thanksgiving Church Service under the theme "Our Heritage... Our Legacy... Our Strength". It was held at the Andrew's Memorial Seventh-day Adventist Church on Saturday, October 8, 2016.
Keywords: Programmes. -- Jamaica